Pendekatan Hermeneutika Dalam Studi Hukum Islam - Pathurrahman Pathurrahman (Universitas Islam Negeri Mataram, 2018)
The following paper examines the methodology and approach of Islamic Jurisprudence studies. According to the author the urgent need of the study and the develop of Islamic Law nowadays is considering not only applying normative / theological approach but also hermeneutics approach. The characteristics of hermeneutics as approach or methodolody in Islamic studies is the text either that of holy scripture or that of anyform is cultural product, polyphonics and open to interpret by many interpreters in accordance with situation, condidtion, culture and historical challenge of human. Accordingly, Islamic Law thought constitutes as opened texts and closed relation to historical and cultural background where the texts produced, so fikih should be reinterpreted, reconstructed and given new alternation in order to be able to answer the problem of law nowadays.